Intensi?cation of Reutealis trisperma biodiesel production using infrared radiation: Simulation, optimisation and validation - Silitonga A.S.; Mahlia T.M.I.; Kusumo F.; Dharma S.; Sebayang A.H.; Sembiring R.W.; Shamsuddin A.H. (Elsevier Ltd, 2023)
Energy utilization; Esters; Infrared radiation; Mass transfer; Transesterification; Biodiesel production; Box-Behnken design; Box-Behnken experimental design; Catalyst concentration; Infrared radiation methods; Physicochemical property; Response surface methodology; Transesterification process; Biodiesel; biofuel; chemical compound; chemical reaction; design method; dicotyledon; essential oil; infrared radiation; model validation; optimization; physicochemical property; response surface methodology; simulation; temperature effect; Reutealis trisperma